PERTUMBUHAN KULTUR KONSORTIUM DALAM MINYAK SELAMA BIODEGRADASI DI BAWAH KONDISI AEROB - Marlinda Nilan Sari Rangkuti; Palsan Sannasi; Sahilah Abdul Mutalib (Universitas Negeri Medan, 2018)
This study reported the ability of the Consortium Culture (5% v/v) was grown in minimum salts medium (MSM) with the addition of 1% (v / v) crude oil, at different incubation times (0, 2, 4, 6 and 8 weeks). The Consortium Culture (CC) can live and use crude oil as the sole source of carbon and energy. The analysis result shows that the highest percentage of biodegradation is at the second week with the percentage of hydrocarbon residue of 42% and it has been used up in the eighth week. These results indicate that the consortium culture can be utilized as a biodegradation agent and this phenomenon can used to enhance the bioremediation ability of the petroleum hydrocarbon polluted environment.